Effectiviness of Red Ginger Nanoparticles on Primary Dysmenorrhea Pain in Adolescent Girls - Yulia Ayuningsiih; Supriyadi Supriyadi; Sri Sumarni (Universitas Malahayati, 2026)
ABSTRACT Every month, adolescent girls experience painful menstruation (dysmenorrhea), which is caused by high levels of the hormone prostaglandin. High levels of prostaglandin cause uterine contractions during menstruation, resulting in pain. The prevalence of dysmenorrhea reaches 90%, with some experiencing severe pain that interferes with daily activities. Therefore, alternative treatments are needed to address the pain of dysmenorrhea. One such treatment is red ginger, as it contains gingerols, shogaols, and flavonoids, which can help relieve dysmenorrhea. Proving the effectiveness of red ginger nanoparticles in reducing the intensity of primary dysmenorrhea pain. This type of research is a true experiment with a pre-test and post-test with a control group design. The population in this study were adolescent girls experiencing primary dysmenorrhea and mild anemia in the Midwifery Department of Poltekkes Semarang. This study was conducted on two groups: the intervention group was given red ginger nanoparticles at a dose of 500 mg 3x2 daily for 14 days; and the intervention group was given red ginger nanoparticles at a dose of 500 mg 3x2 daily for 14 days. The results of the study showed that red ginger nanoparticles were significantly able to reduce the intensity of dysmenorrhea pain, with the results of the Mann Whitnay test statistical test obtaining a p value of 0.000. Red ginger nanoparticles are effective in reducing the intensity of primary dysmenorrhea pain and can be a complementary approach in obstetric practice to reduce dysmenorrhea symptoms. Keywords: Adolescent Girls, Primary Dysmenorrhea, Red Ginger Nanoparticles.